Proceedings of the 3rd symposium on middle ear mechanics in research and otilogy : (World scientific, 2004)
This book aims to facilitate the exchange of ideas between otosurgeons and engineers on common topics such as middle ear function, tympanoplasty, implantable hearing devices and ear prostheses. Due to recent advances in technology, gene-therapy and tissue-engineering procedures will also be important issues in the treatment of middle ear disease.